Evaluation on the implementation of KTSP curriculum based on stake’s countenance model in Arabic subject in the Madrasah Aliyah GUPPI Kota Jambi 2012/2013 - Sanjaya, Budi; Lubis, Maimun Aqsha (Universiti Kebangsaan Malaysia, 2013)
Level of Education Curriculum Unit (KTSP) or Curriculum 2006 are planned and implemented by the education unit, aimed to make schools autonomous. Arabic subjects as compulsory subjects taught religious school at all levels, starting from the Madrasah Ibtida'iah (MI), Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA), including private madrasah (MAS) GUPPI in the City of Jambi. The focus of assessment in this study is to evaluate the implementation of intrinsic evaluation KTSP covering curriculum components and identify teachers' understanding of curriculum, planning, learning Arabic in MAS GUPPI Jambi city. Methods used in data collection is to use observation, interviews, and document analysis. Qualitative data were analyzed using an evaluation Stake’s Model (Stake’s Countenance Model-CSM), which consists of description matrix and judgement matrix. The results showed that the implementation of the MAS GUPPI KTSP Jambi City has done well. Starting from the operational readiness of human resources, planning documents KTSP, and also the ability of teachers in making the syllabus and Teaching Program Plan (RPP) in learning Arabic.